Controle de frequência por meio da geração eólica operando como gerador síncrono virtual considerando a otimização do ponto de operação da turbina eólica - Tessaro, Heitor Jose (2018)
The penetration of wind generation has grown significantly in many countries in the last decades. As a result, the frequency dynamic response and stability have become a concern for power system operators. Thus, this work proposes an operational and control approach for wind generation units based on fully rated converter in order to simultaneously provide inertial response, primary frequency control, and secondary frequency control for power systems with high penetration of wind generation. The proposed control approach, based on virtual synchronous generator, also enables the wind generation to operate as a grid former (frequency control mode). The parameter tuning of the virtual synchronous generator is made through an optimization process which aims to improve the system frequency response, ensuring that the operational limits of the converter employed in the wind generation units are not violated. The assessment of the impact of the proposed control approach on the electromechanical dynamics of the wind generation units is also one of the contributions of this work. The main novel contribution of this work is the proposition of an optimization formulation which optimizes the operating point of the wind generation, in order to reduce the deviation magnitude of the wind turbine speed after load variations. As a result, the optimization reduces the magnitude and settling time of mechanical dynamics of the wind turbine, gearbox, and generator. The results have shown that the proposed control approach is effective in the provision of inertial response and frequency regulation support. The analyses have also showed that the proposed control action resulted in suitable electromechanical dynamics for the wind generation unit. The proposed optimization approach has significantly reduced the deviation magnitude and settling time of the wind turbine speed after load variations.